PENGARUH DUKUNGAN ORANG TUA, JUMLAH JAM BELAJAR DI RUMAH, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR GEOGRAFI SISWA DI SMA NEGERI KABUPATEN KERINCI - Santi Mareta (STKIP Rokania Pasir Pangaraian, 2020)
This study aims to obtain information, analyze and discuss data about the Effects of Parental Support, Number of Hours of Study at Home, and Learning Motivation Against Student Geography Learning Outcomes in Kerinci Regency High School The research method used is a path analysis method to describe and test the relationship model among the variables that are in the form of cause and effect. The study population was all students of class XI IPS scattered in SMA Negeri Kerinci Regency 2014/2015 academic year, totaling 765 people. The sample in this study was taken using the Cluster Sampling (sampling area) technique, obtained a sample of 4 schools namely SMAN 2 Kerinci, SMAN 4 Kerinci, SMAN 7 Kerinci and SMAN 12 Kerinci, from the four schools the sample was taken with a proportion of 25% so that the sample numbered 82 people. The results of the study are as follows: (1) there is a direct influence of parental support on geography learning outcomes that is equal to 4.98%, (2) there is a direct influence of the number of study hours on geography learning outcomes that is equal to 8.35%, (3) there are the direct effect of learning motivation on learning outcomes is 18.32%, (4) there is a direct influence of parental support on student motivation that is equal to 22.56% and (5) there is a direct effect on the number of hours of learning on student motivation that is equal to 20 0%. (6) Government efforts to improve geography learning outcomes, namely by increasing parental support, increasing hours of study at home and increasing learning motivation